Penerapan Program Edukasi Manajemen Limbah di Kawasan Pesisir Pantai Sekupang Batam - Jufri, Muhammad; Dwipananda, Rizki Fadhel; Aswirawan, Maria Yosefina Meinadia Sekar Kinanti; Mustofa, Stevian (Penerbit Goodwood, 2024)
Purpose: The purpose of this service is to educate the community or beach visitors about waste management through collaboration with various related parties. Method: Survey approach. Educational program for the community in the coastal area of ??Batam, especially on Tanjung Pinggir Beach, Sekupang, Batam. Result: This program has succeeded in increasing public awareness of the importance of protecting the environment, so that the next arrival there are already trash cans based on categories and less trash is scattered. Conclusions: The educational program that has been implemented has shown positive results in raising public awareness about the dangers of plastic waste and reducing its usage among coastal communities. Through various educational activities such as socialization, workshops, and environmental campaigns, the community now has a better understanding of the negative impacts of plastic waste on coastal ecosystems and human health. Limitations: Only carried out in one place, namely Tanjung Pinggir Beach, Sekupang Contribution: Increasing public awareness and action in maintaining the cleanliness and sustainability of the coastal environment. Supporting beach managers in environmental conservation efforts.